5x+6+(x-3)=(5+x)-4 решите уравнение

5x+6+(x-3)=(5+x)-4 решите уравнение

  • 5x+6+(x-3)=(5+x)-4
    5x+6+x-3=5+x-4
    5x+2=0
    x=-2/5

    (3+а)^2-(a-4)^2=(3+a+a-4)(3+a-a+4)=(2a-1)*7=14a-7=14*(-3/2)-7=-28

    5(x+3)>7(x+1)
    -5-1.25x<0 5x+15>7x+7
    1.25x>-5

    2x<8
    x>-5/1.25

    x<4
    x>-4

    x(-4;4)

  • 1
    5x+6+x-3=5+х-4
    6x-x=1-3
    5x=-2
    x=-0,4
    2
    9+6a+a-a+8a-16=14a-7
    a=-3/2 14*(-3/2)-7=-21-7=-28
    3
    5x+15>7x+7-2x>-8x<4
    -1,25x<5x>-4
    x(-4;4)